Legal Regulation Of The Use Of Technology In Elementary School Learning - Siti Hapsah Pahira; Rio Rinaldy; Labisal Fitri Al-qalbi; Amelia Amelia (Jurnal Indonesia Sosial Teknologi, 2023)
Nowadays, technology is essential in various aspects of life, including education. Education is the right of all members of society, and the government is obliged to organize education to educate the nation's life. However, besides having a positive impact, technology can also have a negative impact. Thus, there is a need for legal protection against the negative impact of technology use on learning in elementary schools. The purpose of this study is to determine the legal regulation of the use of technology in learning in elementary schools. This research uses a qualitative approach and the Miles and Huberman interactive analysis model, which consists of 3 main things: data reduction, data presentation, and conclusion drawing. The results show that the use of technology in learning in primary schools requires legal regulations that maintain a balance between educational innovation and the protection of students' data. This regulation is essential to regulate the use of technology as a supporting tool, improve learning effectiveness, and create a safe environment. The protection of students' data and cybercrime monitoring should also be integrated into the regulation to create an efficient and ethical education in the digital era.